Serum alkaline phosphatase in hypophosphatasia - Warshaw, Joseph B. (1971)
It is recognized that serum alkaline phosphatase may reflect enzyme contributions from bone, liver, and intestine. We have investigated serum alkaline phosphatases in two siblings with hypophosphatasia. After administration of long-chain triglycerides, the major alkaline phosphatase component of their sera was shown to be of intestinal origin on the basis of inhibition by l-phenylalanine. Starch block electrophoresis suggested that there were other regions of l-phenylalanine-sensitive alkaline phosphatase in addition to the major slow-moving intestinal band. Medium-chain triglycerides which are absorbed by the portal route did not cause a similar augmentation of intestinal alkaline phosphatase activity. These studies indicate that serum levels of intestinal alkaline phosphatase are increased normally after long-chain fat feeding in hypophosphatasia and may be the major component of total serum alkaline phosphatase activity.